1991
DOI: 10.1007/bf02190624
|View full text |Cite
|
Sign up to set email alerts
|

Selection for local adaptation in a plant breeding programme

Abstract: Regressions of yields of cultivars upon means of sets of cultivars over diverse environments are often used as measures of stability/adaptability. Prolonged selection for performance in environments of high yield potential has generally led to unconscious selection for high regressions. If adaptation to poor environments is required (as it often is in Third World agriculture), common sense suggests that low regressions could be exploited for the purpose. Simulations show that systematic selection in the poor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0
15

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(106 citation statements)
references
References 17 publications
3
88
0
15
Order By: Relevance
“…Selection and improvement under optimal conditions may not be suitable for the target areas prone to abiotic constraints (Simmonds, 1991). Therefore, in order to achieve improved and stable yields in stress prone environments it is desirable to improve tolerance to major abiotic constraints prevalent in target environment.…”
Section: Introductionmentioning
confidence: 99%
“…Selection and improvement under optimal conditions may not be suitable for the target areas prone to abiotic constraints (Simmonds, 1991). Therefore, in order to achieve improved and stable yields in stress prone environments it is desirable to improve tolerance to major abiotic constraints prevalent in target environment.…”
Section: Introductionmentioning
confidence: 99%
“…Type-3 stability depends on the measurements of unpredictable irregularities in the response to environment as provided by the deviation from regression (because the regression part is predictable (Eberhart and Russel, 1966)). Static (Type 1) stability may be more useful than dynamic in a wide range of situations, which characterise farming systems in developing countries (Simmonds, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Plant Grond 2003, 20(1) adapted to moisture stressed environments. Breeding and selection under non-stressed conditions may not result in genotypes adapted to stressed environments in the target areas (Rosielle & Hamblin, 1981;Simmonds, 1991). Various trials have shown that moisture stress reduces grain size and seed number per ear, but this may to some degree be compensated by increased number of tillers (Wenzel, 1997;.…”
mentioning
confidence: 99%